Salmonella Heidelberg Isolated from Poultry Shows a Novel Resistance Profile - Neves, Gabriella Bassi das; Stefani, Lenita Moura; Pick, Eduarda; Araujo, Denise Nunes; Giuriatti, Jéssica; Percio, Cleverson; Brisola, Maiara Cristiane (Acta Scientiae Veterinariae, 2016)
Background: The development of antimicrobial resistance in bacteria is a serious public health issue worldwide. Salmonella spp. is considered a leader cause of gastrointestinal disease in animals and humans, and poultry products have been reported as an important reservoir of the bacterium. S. Heidelberg became lately one of the most prevalent serovars found in several countries. However, hardly any information is available about the epidemiology and the resistance profile of it. Therefore, the objective of this study was to determine the antibiotic resistance profile of S. Heidelberg (SH) and to compare to S. Enteritidis (SE) and S. Typhimurium (ST) isolated from the Southern part of Brazil. Materials, Methods & Results: A total of 162 Salmonella isolates of poultry origin serotyped as SH (54), SE (54), and ST (54) were submitted to the disk-diffusion test with disks containing 10 antibiotics of 7 different classes, routinely used in veterinary and human medicine such as: enrofloxacin, ciprofloxacin, norfloxacin, gentamicin, ceftiofur, ceftriaxone, nalidixic acid, tetracycline, sulfamethoxazole-trimethoprim, and chloramphenicol. In addition, the Multi-drug Resistance Pattern (MDRP) and the Multiple-Drug Resistance Index (MDRI) were determined. The Chi-square (χ2) test with 1% of significance level was used to statistically evaluate the results. All isolates were susceptible to norfloxacin, enrofloxacin, and ciprofloxacin. The majority of the isolates were resistant to the quinolone class (68%), more specifically to nalidixic acid, which is considered a synthetic quinolone, followed by penicillin (47%) and cephalosporin (16%). Overall, SH isolates showed higher resistance compared to ST and SE (18, 16.5, and 9.6%, respectively). SH isolated from field samples, mainly drag swabs, showed higher resistance levels (24.2%) than those isolated from slaughterhouses (5.6%). SH showed the highest percentage of resistance to ceftiofur (31.5%), ceftriaxone (9.3%), and tetracycline (64.8%) in comparison to the other two serotypes. Most of the SH isolates were resistant to at least two (66.7%), three or more antibiotics (33.3%). A different scenario was observed for ST and SE, where 25.9 and 9.3% were susceptible to at least one drug, respectively. The most common pattern of resistance (MDRP) was C (gentamicin - nalidixic acid - tetracycline) for 14 SH isolates, and A (ceftiofur - nalidixic acid - tetracycline) for 12 SH isolates. MDRI indicated that 22.8% of all isolates were multidrug resistant. SH was the isolate with the largest variety of resistance patterns compared to ST and SE, where 11.7% of the isolates were resistant to more than three antibiotics. In addition, SH showed the greatest MDRI (0.25) ranging from 0.2 to 0.5. Discussion: SH was resistant to almost all antibiotics tested and showed multi-drug resistant profile, therefores, it showed a potential for horizontal transmission of resistance genes. Additionally, SH showed a higher resistance profile for ceftiofur, an important antibiotic used in poultry, which can cross-resist to ceftriaxone, commonly used to treat salmonellosis in children. Our results showed that SH is a real challenge regarding antimicrobial resistance. This scenario leads to the need for rational and judicious use of antimicrobials in poultry and, as an alert to the medical community.